EVALUATING THE IMPACT OF SPINAL AND GENERAL ANESTHESIA ON NEONATAL APGAR SCORES IN ELECTIVE CAESAREAN DELIVERIES - Dr Mehdi Hussain; Dr Ijaz Hussain; Dr Muhammad Adil Jadoon (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective To compare the impact of general anesthesia and spinal anesthesia on neonatal Apgar scores in patients undergoing elective cesarean sections. Methodology This study conducted at the Departments of Anesthesia, District Headquarter Hospital Parachinar and Mahmood Hospital Parachinar, from August 2023 to April 2024, investigated the impact of spinal anesthesia versus general anesthesia on neonatal Apgar scores in 110 ASA II patients with normal pregnancies and no comorbidities, undergoing elective Cesarean sections. Participants were assigned to receive either spinal anesthesia (Group I) or general anesthesia (Group II) – based on their personal preferences. Apgar scores at 1 and 5 minutes post-delivery were the primary outcomes measured. Statistical analysis showed significant differences favoring spinal anesthesia in terms of Apgar scores. Ethical standards were rigorously followed, with approval from the Ethics Board and informed consent from all participants. Results This study compared neonatal outcomes between 110 patients undergoing cesarean section under either general anesthesia or spinal anesthesia. Demographic characteristics including age, height, weight, gestational age, and fetal weight were well-matched between groups. Surgery time was shorter in the spinal anesthesia group (53.2 vs. 56.9 minutes), while anesthesia duration was similar. Infants born under spinal anesthesia had significantly higher Apgar scores at 1 minute (8.05 vs. 7.15) and 5 minutes (9.30 vs. 8.90) compared to those born under general anesthesia (p < 0.001). A greater percentage of infants in the spinal anesthesia group achieved Apgar scores of 7 and above (96.4% vs. 83.6%) with fewer scoring below 7 (3.6% vs. 16.4%) compared to the general anesthesia group. Conclusion Based on the study’s results, spinal anesthesia emerges as a superior choice in elective cesarean sections, associated with higher Apgar scores and greater maternal satisfaction compared to general anesthesia.